The Italian secretary : a further adventure of Sherlock Holmes - Carr, Caleb, 1955- (New York : Carroll & Graf, 2005)
Legendary detective Sherlock Holmes finds himself on the trail of a murderer whose connections may run all the way up the social ladder to the royal family.
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Criminal psychology -- Fiction; Mystery fiction